If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -4x = 7x + -9 + -8 Reorder the terms: 6 + -4x = -9 + -8 + 7x Combine like terms: -9 + -8 = -17 6 + -4x = -17 + 7x Solving 6 + -4x = -17 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + -4x + -7x = -17 + 7x + -7x Combine like terms: -4x + -7x = -11x 6 + -11x = -17 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + -11x = -17 + 0 6 + -11x = -17 Add '-6' to each side of the equation. 6 + -6 + -11x = -17 + -6 Combine like terms: 6 + -6 = 0 0 + -11x = -17 + -6 -11x = -17 + -6 Combine like terms: -17 + -6 = -23 -11x = -23 Divide each side by '-11'. x = 2.090909091 Simplifying x = 2.090909091
| 5x^2+25x+30=-5x^2 | | 3x(-12)-6=4x | | 4+1-3m-3m=-2m-3m | | 1.2(7.2-0.3x)=-4.1x | | 4x-3(-2x+5)=40 | | 2x^2+3x-24=0 | | x^2-24x+50=-8x+2 | | x+2x+(x-12)=180 | | -(8y+2)-(7y-5)=-1 | | 9-1/2(3n-6)=n+2 | | 20n+4=24n-40 | | 2b+4=9+3b | | 5(x-2)=10(2-x) | | 0=z^2-(1+2i)z-x+2i | | 1+6x+3=5x+2 | | 0.5x^2-6=x^2+4x | | 4x+8+3x+9=13 | | f=-9+16 | | 15-8*2+12= | | -7p-4=-2p-14 | | 2[4-2(3-x)]-1=4[2(x-3)+7]-25 | | 99-4b=-11b | | 1+1+7a+3=a-1+4a | | .75k-.75=7 | | -8+b=4 | | x*5=x+4 | | 5x+45-3x=15 | | x+(x+5)+x+(x+5)=86 | | 2.25-.25g=.50g | | 5x+45+3x=15 | | 23x^2+22x=0 | | s^2=18-3s |